Intraspecific variation in megalopae of Clibanarius antillensis (Anomura, Diogenidae) among western Atlantic populations - Cházaro-Olvera,Sergio (2018)
ABSTRACT The objective of this study was to describe the morphology of Clibanarius antillensis Stimpson, 1859 megalopae collected in the vicinity of Isla Sacrificios, Mexico, and compare it to previous descriptions originated from Brazilian and Panamanian specimens raised in laboratory conditions. We found four meristic differences between the Brazilian and the Panamanian and Mexican populations with the Brazilian population: the outer flagellum of antennule in the Panamanian and Mexican populations has more aesthetascs on the second, third, and fourth segments of the outer flagellum (0, 6, 5, 3, 0) than the Brazilian population (0, 4, 4, 2, 0); the maxilla has more setae on the scaphognathite in the Brazilian specimens (70) than in the Mexican and Panamanian specimens (49-62); the crista dentata of the third maxilliped is formed by only three denticles in the Brazilian specimens, while 4 or 6 denticles form the same structure in the Panamanian and Mexican populations; there are fewer number of setae on the endopod of the uropod in the Brazilian population. The differences may be explained by intraspecific variation.